Short-term effects of cover crop inclusion under no-tillage management on soil physical quality = Efectos de corto plazo de la inclusión de un cultivo de cobertura bajo siembra directa sobre la calidad física del suelo - Villarreal, Rafael; Lozano, Luis Alberto; Melani, Esteban; Polich, Nicolás Guillermo; Salazar, María Paz; Bellora, Guido Lautaro; Soracco, Carlos Germán (Asociación Argentina de la Ciencia del Suelo, 2024)
Integrating cover crops (CC) in the crop sequence could lead to an enhancement of the notillage (NT) performance improving soil physical quality (SPQ). The objectives of this work were: i- to determine the SPQ on different moments of the crop cycle during the first year after incorporation of cover cropping (barley and vetch) (CC), as compared with bare fallow (BF); and ii- to measure the impact of cover crops on the top soil water content during the first year of its introduction. SPQ indicators were determined from the soil water retention curve (SWRC) and in-situ infiltration data in different dates during the first year after inclusion of CC. The experiment was carried out in a fine, illitic, thermic abruptic Argiudoll. For both treatments, maize was sown as summer crop. CC management showed higher values of plant available water content (PAWC) and Dexter index (S), and lower values of bulk density (BD) as compared with BF. Higher values of field capacity (FC) under CC were observed during the maize growing season. On the other hand, no differences between treatments were observed for Pmac. These results show that the inclusion of CC under NT management improves the soil capacity to retain water and counteract compaction processes under NT. At the end of the crop cycle, higher values of water-conducting macroporosity (εma) and macropore connectivity (Cwma) were observed under CC. Higher values of soil water content during the maize growing period were observed under CC, showing that the inclusion of CC has no negative effects on the top soil water content. Our results show that the inclusion of CC is an opportunity for intensify crop sequences in the Argentinean Pampas Region, oriented to enhance the performance of NT.